2013
DOI: 10.4084/mjhid.2013.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heterogeneity of Beta Globin Mutations Among Asian-Indians and Importance in Genetic Counselling and Diagnosis

Abstract: There are an estimated 45 million carriers of β-thalassemia trait and about 12,000–15,000 infants with β-thalassemia major are born every year in India. Thalassemia major constitutes a significant burden on the health care system. The burden of thalassemia major can be decreased by premarital screening and prenatal diagnosis. The success of prenatal diagnosis requires proper knowledge of spectrum of β-thalassemia mutations. In present study, β-thalassemia mutations were characterized in 300 thalassemia cases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The inherited disorders of hemoglobin, particularly the βthalassemia and their interaction with hemoglobin S (HbS) are a considerable health problem in India and contribute significantly to morbidity and mortality. Earlier studies have shown that the overall prevalence of β-thalassemia is 3-4 % with an estimate of around 8,000 to 10,000 new births with major disease each year [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The inherited disorders of hemoglobin, particularly the βthalassemia and their interaction with hemoglobin S (HbS) are a considerable health problem in India and contribute significantly to morbidity and mortality. Earlier studies have shown that the overall prevalence of β-thalassemia is 3-4 % with an estimate of around 8,000 to 10,000 new births with major disease each year [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…IVS I‐5 (G>C) has remained the predominant mutation in all these studies with regional variations in frequencies of the other common mutations. The distribution of mutations reported from different states in India has been collated in a few studies . A meta‐analysis on 17 selected studies comprising 8505 alleles nationally showed that 52 mutations represented 97.5% of all the β thalassemia alleles with IVS I‐5 (G>C) varying from 44.8% in the north to 71.4% in the east …”
Section: Discussionmentioning
confidence: 99%
“…The distribution of mutations reported from different states in India has been collated in a few studies. [32][33][34] A meta-analysis on 17 selected studies comprising 8505 alleles nationally showed that 52 mutations represented 97.5% of all the β thalassemia alleles with IVS I-5 (G>C) varying from 44.8% in the north to 71.4% in the east. 33 There are a few recent reports of novel mutations as well like Codon 2 (−A), −42 (C>G), and −223 (T>C) from eastern India 35 and Codon 53 (C>T) from West Bengal.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports from North India have emphasized the need for regular evaluation of the mutation, as the shift in the frequencies of the mutation is very high [ 5 , 6 , 8 , 9 ]. Thereby we have analyzed the spectrum of mutation in different neighboring states or country.…”
Section: Discussionmentioning
confidence: 99%
“…In India the social factors such as preference to marry within the community and among 1st degree relatives (consanguinity) is quite prevailing and thus plays an important role in increasing the gene pool of the mutation responsible for disease within the community [ 5 , 8 , 9 ]. In that scenario target oriented prenatal diagnosis helps early detection of the fetus status.…”
Section: Introductionmentioning
confidence: 99%